If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + Y = 49 Solving 14 + Y = 49 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + Y = 49 + -14 Combine like terms: 14 + -14 = 0 0 + Y = 49 + -14 Y = 49 + -14 Combine like terms: 49 + -14 = 35 Y = 35 Simplifying Y = 35
| 3(4x-8)=31-4(x+2) | | 2w+18-3w-5=18 | | 21-9f=(-20f-6) | | 4v+16=56-v | | 4x^2-54x+110=0 | | 18n-6=19n-8 | | 49v+7=4v-18+70 | | 7r-16=2r-1 | | 10p-3=2p+21 | | x-3-6x=-3x-7+5x | | (3x-2)(3x-2)=15 | | 4y^2+9u+2=0 | | 7x+8=x+32 | | 14y+16=48-15+18 | | 3/8(x-4)=24 | | y=17+-7x | | y=x^2+7x-2 | | -8xy+-12xy= | | 1/2x-3=14/5-3/4x | | 17f^2+7f=0 | | 2=0.6x^2+3x+4 | | 12x-10=12-4x | | u-3+10u+6=102 | | 0=0.6x^2+3x+6 | | 1/4y-6=1/10y | | 2(x+2)=85 | | 20x-2=12x+7 | | 5(10x+25)=575 | | -96=4u-10-27u+6 | | x/-0.168=0.08 | | 3/5w=8/9 | | 2x-3(5-x)=20 |